Angel with two faces: a mystery featuring Josephine Tey (Josephine Tey, 2,, 2010)
Description Not Provided

Two for sorrow (Josephine Tey mystery, 3,, 2010)
Description Not Provided

Fear in the sunlight (Josephine Tey mystery, ,, 2013)
It's summer, 1936. The writer, Josephine Tey, joins her friends in the holiday village of Portmeirion to celebrate her fortieth birthday. Alfred Hitchcock and his wife, Alma Reville, are there to sign a deal to film Josephine's novel, "A Shilling for Candles", and Hitchcock has one or two tricks up his sleeve to keep the holiday party entertained.

The death of Lucy Kyte: a Josephine Tey mystery (Josephine Tey, 5,, 2014)
In this atmospheric, intriguing historical mystery brimming with psychological tension, an unexpected inheritance plunges beloved British mystery author Josephine Tey into a disturbing puzzle of dark secrets eerily connecting the present and the past.

London rain: a new mystery featuring Josephine Tey (Josephine Tey mystery, 6,, 2016)
"Intrepid writer and amateur sleuth Josephine Tey returns in this sixth installment of Nicola Upson's popular series--perfect for fans of Agatha Christie's Hercule Poirot and Jaqueline Winspear's Maisie Dobbs--that unfolds in 1930s London as England prepares to crown a new king.London, 1937. Following the gloomy days of the abdication of King Edward VIII, the entire city is elated to welcome King George. Just one of the many planned festivities for the historic coronation is a BBC radio adaptation of Queen of Scots, and the original playwright, Josephine Tey, has been invited to sit in on rehearsals. Soon, however, Josephine gets wrapped up in another sort of drama. The lead actress has been sleeping with Britain's most venerable newsman, Anthony Beresford--and his humiliated wife happens to work in the building. The sordid affair seems to reach its bloody climax when Beresford is shot to death in his broadcasting booth at the deafening height of the coronation ceremony. Josephine's dear friend, Detective Chief Inspector Archie Penrose, has the case wrapped up before long. But when a second, seemingly related murder throws Penrose for a loop, it falls to Josephine to unravel a web of betrayal, jealousy, and long-held secrets... caught all the while in a love triangle of her own making. Charming and provocative, thick with the atmosphere of prewar England, London Rain is a captivating portrait of a city on the edge--and an unforgettable woman always one step ahead of her time"-- "May, 1937, London: The country is still reeling from Edward VIII's shocking decision to abdicate the throne in order to marry the woman he loves, Wallis Simpson. As London prepares for the historic Coronation of his brother, George, bestselling writer Josephine Tey is in town to oversee a BBC radio production of her play, Queen of Scots. When one of the BBC's best-known broadcasters is murdered at the height of the Coronation celebrations, Josephine has a front row seat. Detective Chief Inspector Archie Penrose is called to investigate--and then another killing occurs. The victim? The leading actress in Josephine's play, who happened to be the broadcaster's mistress. Adultery, treachery, and pent-up jealousies clearly haunt the BBC, suggesting the motive lies close to home, but Josephine suspects that the killings are linked to a decade-old scandal. His hands tied by bureaucracy and his attention taken by another, seemingly unrelated death, Archie is unable to solve the case. It's up to Josephine to untangle a long-hidden web of love, deceit and betrayal. As her own relationship with Marta Fox reaches a turning point, she must confront the consequences of romance gone awry"--

Sorry for the dead: a Josephine Tey mystery (A Josephine Tey mystery, 8,, 2019)
"In the summer of 1915, the sudden death of a young girl brings grief and notoriety to Charleston Farmhouse on the Sussex Downs. Years later, Josephine Tey returns to the same house--now much changed--and remembers the two women with whom she once lodged as a young teacher during the Great War. As past and present collide, with murders decades apart, Josephine is forced to face the possibility that the scandal which threatened to destroy those women's lives hid a much darker secret."--Amazon.

The secrets of winter (Josephine Tey mystery, 9,, 2020)
Josephine and Archie gather with friends to celebrate the holidays on 1938 Cornwall’s stormy coast before the festivities are interrupted by two brutal deaths on St. Michael’s Mount and the arrival of a world-famous film star.

Dear little corpses (Josephine Tey mystery, 10,, 2022)
"During the mass evacuation from London in September 1939, a little girl vanishes without a trace and Josephine struggles with the chaos and uncertainty of war"--

Shot with crimson (Josephine Tey mystery, ,, 2023)
In 1939 Hollywood, Josephine Tey, when a shocking act of violence on the set of Hitchcock's Rebecca reawakens the shadows of the past, teams up with DCI Archie Penrose and together, they follow a trail of clues that echoes Rebecca's timeless themes of obsession, jealousy and murder.